Assessment of Acceptable Swiss post-2012 Climate Policies - André Sceia; Juan-Carlos Altamirano-Cabrera; Marc Vielle; Nicolas Weidmann (Swiss Journal of Economics and Statistics, 2012)
In the framework of the revision of the Swiss CO2-Law and in the preparation of the international negotiations that place at the Conference of the Parties to the United Nations Framework Convention on Climate Change, the Swiss Government has proposed a set of instruments and two levels of abatement to define the Swiss climate policy for the post-2012 period. By 2030, Switzerland would recuce its GHG emission by 30% or 45%, depending on whether or not the rest of the world world would commit to strong emissions reductions. The proposed policies are the result of consultation procedures take into account the views of major stakeholders and lobbies and allow for differienciated carbon prices in different sectors of the Swiss economy. Linking a Cumputable General Equilibrium (CGE) and two sectoral energy models, we evaluate the policies for the two scenarios. We find important disparities in the prices of carbon faced by the different economic sectors and higher welfare costs than those that would be triggered by a uniform carbon tax.
Keywords: C68; D58; Q54; N70; 330; Climate policy; Environmental taxation; Hybrid modeling; Transport; Residential; Welfare economics